Aníbal Zambrano, M.D: a Peruvian physician with a heart of gold - Ponce-Rosas, Linda (2022)
The objective of the article is to describe and analyze the life trajectory and the humanitarian contributions of Dr. Zambrano, a physician who graduated from San Fernando Medical school, and was president of the Center for Medical Students at a politically critical time in public university education. He emigrated to the United States in 1970, in the context of sociopolitical crisis in Peru and the world, where he became a renowned internist and cardiologist at St. Luke’s Hospital. Despite the distance, he maintained a close relationship with Peru, organizing multiple medical missions for underserved populations, training medical personnel, and providing technological implementation to Cajamarca Regional Hospital. In 2011, the Educational Medical Center was inaugurated in Chincha, with Zambrano being one of the leaders for its construction. Despite suffering from a disabling illness, he dedicated until the last days of his life, providing help for those most in need. His life trajectory shows us an example of commitment to Peru and practice of Medicine committed to solidarity and the development of Medicine in his country of origin.